MSMEs' Contribution in Encouraging the Improvement of Community Welfare - Agus Santoso; Trie Hierdawati; Ermaini Ermaini; Rian Dani (International Journal of Economics and Management Sciences, 2025)
Welfare is crucial in the economy, indicating that people are able to meet their basic needs, such as food and clothing. Moreover, the existence of micro, small, and medium enterprises (MSMEs) greatly supports the achievement of this welfare by providing economic opportunities that help people access their living needs. The purpose of this study is to determine the role of micro, small, and medium enterprises (MSMEs) in improving community welfare. The research method used is descriptive qualitative using a literature study approach supported by secondary data. The results of this study reviewed from an economic aspect state that Micro, Small, and Medium Enterprises (MSMEs) play an important role in improving community welfare. The greater the welfare, the better the country's economic growth and development. In addition, there is legal support through various regulations designed to support the development of MSMEs and realize community welfare.